The photo-fluorescence properties of some organic materials - Cameron, Antony John Wesley (Rhodes University, Faculty of Science, Department of Physics and Electronics, 1959)
In this thesis I have given an account of the experimental work carried out by me at Rhodes University from the beginning of 1954 to the end of 1955, and the analysis of the results which was completed during the following two years, 1956 and 1957. The dissertation is divided into two sections; Part I deals with the photo fluorescence spectra of a large group of organic compounds, and Part 2 describes an investigation of the photo-fluorescence properties of and energy transfer in liquid organic solutions.
Keywords: Hydrocarbons -- Spectra -- Fluorescence; Organic compounds; Energy transfer